2018
DOI: 10.4174/astr.2018.94.4.203
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of stoma re-creation after closure of diverting ileostomy in patients with rectal cancer who underwent low anterior resection or intersphincteric resection with loop ileostomy

Abstract: PurposeThe aim of this study was to identify the risk factors of stoma re-creation after closure of diverting ileostomy in patients with rectal cancer who underwent low anterior resection (LAR) or intersphincteric resection (ISR) with loop ileostomy.MethodsWe retrospectively reviewed 520 consecutive patients with rectal cancer who underwent LAR or ISR with loop ileostomy from January 2005 to December 2014 at Chonnam National University Hwasun Hospital. Risk factors for stoma re-creation after ileostomy closure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 29 publications
1
16
0
2
Order By: Relevance
“…Garfinkle et al (31) reported that 8% of patients had complications such as intestinal obstruction after loop ileostomy closure. Song et al (32) reported that in 520 cases of loop ileostomy closure, 9.8% of patients underwent restoma due to postoperative complications. The reasons may include anastomosis-related complications, local recurrence, and loss of anal sphincter function.…”
Section: Discussionmentioning
confidence: 99%
“…Garfinkle et al (31) reported that 8% of patients had complications such as intestinal obstruction after loop ileostomy closure. Song et al (32) reported that in 520 cases of loop ileostomy closure, 9.8% of patients underwent restoma due to postoperative complications. The reasons may include anastomosis-related complications, local recurrence, and loss of anal sphincter function.…”
Section: Discussionmentioning
confidence: 99%
“…Haksal et al [19] reported that anastomosis fistula was one reason for failure of stoma closure (8.3%). Song et al [20] reported that anastomosis leakage was an independent risk factor for stoma re-creation after closure of defunctioning stoma in patient rectal cancer. Also, fistula was involved in leakage.…”
Section: Discussionmentioning
confidence: 99%
“…In different centres, patients are qualified for the closure of LI before, at the time of or after adjuvant treatment. The presence of PS may be caused by no scheduling for closure of LI and the necessity for stoma recreation after the previous closure procedure [7].…”
Section: Introductionmentioning
confidence: 99%